The effects of age, race, and offense type on receiving a ‘youth discount’ in juvenile court - Bryson, Sara L. (Journal of crime and justice, 2022)
Previous research has suggested that younger justice-involved youth are generally viewed as less blameworthy, less cognitively developed, and more likely to respond to treatment or services by the juvenile justice system than their older youth counterparts. As a result, younger juveniles may be more likely to receive lenient treatment at several juvenile court stages compared to older youth (i.e., ‘youth discount’). However, less research has investigated if the ‘youth discount’ is equally applied across racial groups and youth charged with different offenses (i.e., status versus delinquent). Using all individual referrals in a Southern state from 2010-2016, the current study investigates the individual and joint effects of a juvenile’s age, race, and the handling of status offenders across petition and dispositional case outcomes. Results indicate that the youth discount applied at the petition stage but not disposition. The findings also suggest that race and offense type are more predictive of decision-making than the age of the juvenile. We discuss these findings and their implications for understanding the complexities of juvenile justice decision-making.